Building Customer Satisfaction Through Quality of Service and Product Quality At CV. Orange Food Kreasindo Tangerang City - Kasmad Kasmad; Udin Ahidin; Bella Herpina (Greenation Research & Yayasan Global Resarch National, 2023)
This study aims to determine how much the contribution of service quality and product quality in building customer satisfaction at CV Oranje Food Kreasindo in Tangerang City, either partially or simultaneously. The method used is quantitative with a descriptive approach. The sampling technique used the slovin formula and obtained a sample of 100 respondents. The results of the study show that service quality makes a significant contribution to customer satisfaction with a correlation value of 0.834 and a coefficient of determination of 69.6%. Product quality makes a significant contribution to consumer satisfaction with a correlation value of 0.708 and a coefficient of determination of 50.2%. While simultaneously Service Quality and Product Quality contribute significantly to Consumer Satisfaction with a correlation value of 0.842 and a coefficient of determination of 70.8%.